2017
DOI: 10.1111/joss.12243
|View full text |Cite
|
Sign up to set email alerts
|

Organic label's halo effect on sensory and hedonic experience of wine: A pilot study

Abstract: This exploratory pilot study analyzes the influence of organic labeling on the sensory perception of wine, assessing not only overall hedonic rating but specific experiences of different sensory qualities, and addresses the question whether the organic halo effect on hedonic evaluation and purchase intention can be explained by variations in sensory ratings. A sample of 90 consumers took part in a one‐way (organic label vs. control), between‐groups experimental design comprising a wine tasting task and subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 77 publications
5
76
1
Order By: Relevance
“…These findings directly contrast with the findings of many researchers (e.g., Mueller & Szolnoki, ; Olsen et al, ; Torres‐Moreno et al, ; Varela et al, ; Vidal et al, ) who found that information had at least a small impact on overall liking scores. They are also in contrast with findings of a recent study by Apaolaza et al () showing that labeling affects consumer's beliefs. This discrepancy may be explained by the fact the labeled and conventional food products that were analyzed have quite similar taste qualities due to use of the same local/regional ingredients and akin traditional recipes and production process (Kos Skubic, Klopčič, & Erjavec, ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These findings directly contrast with the findings of many researchers (e.g., Mueller & Szolnoki, ; Olsen et al, ; Torres‐Moreno et al, ; Varela et al, ; Vidal et al, ) who found that information had at least a small impact on overall liking scores. They are also in contrast with findings of a recent study by Apaolaza et al () showing that labeling affects consumer's beliefs. This discrepancy may be explained by the fact the labeled and conventional food products that were analyzed have quite similar taste qualities due to use of the same local/regional ingredients and akin traditional recipes and production process (Kos Skubic, Klopčič, & Erjavec, ).…”
Section: Discussioncontrasting
confidence: 99%
“…It does not include a manipulation check addressing whether the participants truly perceived the product they were testing was a labeled product, which could affect the results. Moreover, since the final effect of the label on consumer purchasing behavior is most relevant (Apaolaza et al, ), future studies should also examine the labeling effect on purchase intention. One main limitation is that the study only focused on certain labels related to quality, PDO and PGI in particular.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study with panelists who were uninformed about organic status, panelists exhibit the same liking scores for organic wine and conventional wines, although the authors still estimate that panelists will pay a price premium for the organic wine (Pagliarini, Laureati, & Gaeta, ). On the other hand, Apaolaza, Hartmann, Echebarria, and Barrutia () show consumers express higher hedonic ratings for wine when an organic label is present in addition to believing that organic wine is healthier.…”
Section: Introductionmentioning
confidence: 99%
“…The organic product presented a strong association to the categories “Price” ( p = .001), by the aggregated product's value; “Quality” ( p = .001), by the perception of superior quality; and “Unfamiliarity/mistrust” ( p = .05), showing a low participant's affinity with the mentioned products. Previous studies reported that despite low knowledge about the products, regulations, and certifications, the organic foods are seen as elements of good quality, and although the organic labeling raises the hedonic evaluation and purchase intention, the higher price commercially practiced is still a limiting factor to the consumption and growth of the organic products segment (Apaolaza, Hartmann, Echebarria, & Barrutia, ; Hidalgo‐Baz et al, ; Marian, Chrysochou, Krystallis, & Thøgersen, ). In this context, it is highlighted the need to implement strategies by the sectors involved in the organic dairy marketing chain that make the information clearer and accessible to the consumer, as well as certification mechanisms that guarantee the quality and suitability of these products.…”
Section: Resultsmentioning
confidence: 99%